Preventing effect of different interstitial materials on thermal runaway propagation of large-format lithium iron phosphate battery module. (July 2023) - Yu, Yin; Huang, Zonghou; Mei, Wenxin; Jia, Zhuangzhuang; Song, Laifeng; Wang, Qingsong
Abstract: Thermal runaway propagation (TRP) has become an urgent problem in the field of lithium-ion battery (LIB) fire safety, bringing potential risks to their large-scale applications. In this work, a novel strategy to prevent TRP of large-format lithium iron phosphate battery (LFP) module using aerogel, polyimide foam (PIF) and mica tape composite insulation cotton (MTCC) is proposed and investigated experimentally under two modules. One module consists of three batteries with insulation placed in every other battery (Individual Insulation Module, IIM), and the other module has four batteries with insulation placed in every third battery (Spacer Insulation Module, SIM). The prevention effect of the interstitial materials is analyzed by changing the thickness and configuration type in two modules. In addition, the heat transfer from the front batteries to the last battery under SIM is calculated. The results show that both the aerogel and 2 mm PIF can prevent TRP, and the latter can reduce the heat transfer power from the penultimate cell to the last cell from 785.28 W to 314.2 W. However, PIF and MTCC with 1 mm thickness can only prolong the TRP time by 1351 and 1462 s, respectively. Modules with SIM configuration are less dangerous than those with IIM. The heat from the penultimate battery dominates the temperature rise of the last battery, while the heat transferred from other parts to the last battery only accounts for 10–19 % of the total heat. Highlights: Novel module configuration is designed to explore the effect of insulation materials. The preheat from the front batteries to the last battery is calculated. 2 mm thickness polyimide foam exhibits the most excellent insulting capacity. The penultimate battery dominates the temperature rise of the last battery.